Evaluation of Premarital Counseling Programs at the Office of Religious Affairs in Surakarta - Khairi, Alfin Miftahul (KONSELING RELIGI, 2025)
This study aims to evaluate the implementation of the premarital counseling program at the Office of Religious Affairs (KUA) in Surakarta, particularly through the “Make Me Halalmu” program, in preparing prospective brides and grooms for marriage. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, non-participant observation, and documentation. The research subjects consisted of religious instructors and officials at the KUA Jebres, Surakarta. Data were analyzed using descriptive qualitative techniques. he results show that the implementation of premarital counseling has followed structured stages, including preparation, implementation, and evaluation. The program contributes to improving participants’ understanding and mental readiness for marriage. However, several challenges were identified, such as limited funding, low participant commitment, and constraints in program capacity. The “Make Me Halalmu” program also demonstrates innovation in attracting public interest, although its effectiveness in achieving long-term outcomes remains limited. It is recommended that the KUA strengthen program management, expand participant capacity, and develop more comprehensive and sustainable evaluation mechanisms. Future research is also encouraged to apply more specific evaluation models to assess the effectiveness of premarital counseling programs.